Adjuvant Chemotherapy in Resected Stage II Non-small Cell Lung Cancer: Evaluating the Impact of Dose Intensity and Time to Treatment. Issue 7 (July 2015) - Ramsden, K.; Laskin, J.; Ho, C.
Abstract: Aims: Platinum-based adjuvant chemotherapy is the standard of care for resected stage II non-small cell lung cancer (NSCLC). The purpose of this population-based study was to identify factors that predict for receiving adjuvant therapy and to assess the effect of delayed administration and dose reduction on survival. Materials and methods: The British Columbia Cancer Agency provides cancer care to 4.6 million individuals across a large and varied geographical area. A retrospective review was conducted of all referred patients with resected stage II NSCLC between 2005 and 2010. Baseline characteristics, systemic therapy details and outcomes were recorded. Results: Of 258 stage II NSCLC patients, 158 received adjuvant chemotherapy (61%). No-adjuvant versus adjuvant population: men 52%/57%, median age 67/62, Eastern Cooperative Oncology Group (ECOG) ≤ 1 55%/75%, Charlson comorbidity score (CCS) ≤ 1 61%/74%, pneumonectomy 11%/26%. In patients who received chemotherapy, treatment details were: cisplatin/carboplatin based 81%/19%, median cycles delivered 4, median time from surgery to adjuvant chemotherapy 8 weeks, 72% received ≥ 80% (cisplatin < 256 mg/m 2 and carboplatin < AUC 19.2) total planned dose. On multivariate analysis younger age, better ECOG and pneumonectomy were predictive of adjuvant treatment. Overall survival of adjuvant-treated patients was inferior for those with CCS ≥ 2, age ≥ 70 and reduced dose intensity on multivariate analysis. The surgery to chemotherapy interval did not affect overall survival. Conclusions: Pneumonectomy and factors associated with better functional status predicted for receiving adjuvant chemotherapy. For patients who received adjuvant chemotherapy the total platinum dose given affected survival but time from surgery did not. A higher platinum dose delivery was important in maintaining the efficacy of adjuvant chemotherapy for resected stage II NSCLC in this retrospective population-based study. Highlights: A population-based study of adjuvant chemotherapy in resected stage II NSCLC. Of all patients referred for treatment, 61% received adjuvant treatment. Predictors for adjuvant chemotherapy were age < 70 y, ECOG PS 0-1 and pneumonectomy. Time to adjuvant treatment did not negatively affect survival outcomes. Dose reduction was associated with poorer overall survival.